Menjadi Moderat Melalui Mata Kuliah Al-Islam dan Kemuhammadiyahan di Universitas Muhammadiyah Kendari - Asman, Asman; Yusuf, Yusuf (Al-Adyan: Journal of Religious Studies, 2023)
Religious moderation is increasingly becoming an important issue, considering the reality of religion today is increasingly worrying. This is due to the exclusive way of diversity and feeling that the religious teachings believed are the only true ones. The purpose of this study aims to explain the concept of religious moderation contained in the Al Islam and Kemuhammadiyah course at Muhammadiyah Kendari University. In addition, the concept contained in the AIK course can be used as a tool to see the reality of religious moderation. This research method is a literature study with a descriptive qualitative analysis approach in formulating a research finding. The data sources used are primary and secondary data. The data collection technique used is documentation. In this research, the data analysis technique used is content analysis. The data analysis technique used is the Beruard Barelson model analysis. The results showed that religious moderation through AIK courses at Muhammadiyah University has four important pillars in its application. The four pillars are being fair, caring for others, not hostile to each other, and being able to knit togetherness. These pillars affect students in their daily life. Moderasi beragama semakin menjadi persoalan penting, mengingat realitas keberagamaan saat ini kian mengkhawatirkan. Hal demikian disebabkan cara beragam yang eksklusif dan merasa ajaran agama yang diyakini adalah satu-satunya yang benar. Penelitian ini bertujuan untuk menjelaskan konsep moderasi beragama yang terdapat pada mata kuliah Al-Islam dan Kemuhammadiyahan (AIK) di Universitas Muhammadiyah Kendari. Selain itu, konsep yang terdapat pada mata kuliah AIK tersebut dapat dijadikan sebagai alat untuk melihat realitas moderasi beragama. Metode penelitian ini ialah studi kepustakaan dengan pendekatan analisis kualitatif deskriptif dalam merumuskan sebuah temuan penelitian. Sumber data yang digunakan ialah data primer dan sekunder. Sementara teknik pengumpulan data yang digunakan ialah dokumentasi. Dalam penelitian ini, Teknik analisis data yang yang digunakan ialah analisis isi (content analysis) model Beruard Barelson. Hasil penelitian menunjukkan, moderasi beragama melalui mata kuliah AIK di Universitas Muhammadiyah memiliki empat pilar penting dalam penerapannya. Keempat pilar tersebut ialah berlaku adil, peduli sesama, tidak saling bermusuhan, dan dapat merajut kebersamaan. Pilar tersebut mempengaruhi mahasiswa dalam berlaku pada kehidupan sehari-hari.